1991
DOI: 10.3109/08916939109004816
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Functional Changes in the Thyroid Glands of Mice Implanted With Hybridomas Secreting Monoclonal Autoantibody Against Mouse Thyroglobulin

Abstract: Mouse hybridoma cells secreting monoclonal antibody (mAb) against mouse thyroglobulin were established. The implantation of the hybridomas succeeded to induce high titers of circulating mAb against thyroglobulin in sera of mice. By using the implantation of the hybridomas in mice, the effect of autoantibody on the thyroid glands was studied histologically and functionally. In these mice the thyroid follicles were significantly swollen and warped, whereas there was no infiltration of inflammatory cells. The 125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

1995
1995
2001
2001

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…Our experimental system using KO3 LPS might also provide a new model for autoimmune sialadenitis. A series of experimental autoimmune diseases that have been established by using KO3 LPS adjuvant were characterized by the extensive infiltration of polymorphonuclear leukocytes, suggesting the participation of Arthus reaction [15,21,22,26,35]. In the present study, however, mononuclear cells consisting mainly of small lymphocytes were found at the early stage after immunization and maintained until the late stage.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Our experimental system using KO3 LPS might also provide a new model for autoimmune sialadenitis. A series of experimental autoimmune diseases that have been established by using KO3 LPS adjuvant were characterized by the extensive infiltration of polymorphonuclear leukocytes, suggesting the participation of Arthus reaction [15,21,22,26,35]. In the present study, however, mononuclear cells consisting mainly of small lymphocytes were found at the early stage after immunization and maintained until the late stage.…”
Section: Discussioncontrasting
confidence: 43%
“…The intensity of the adjuvanticity of KO3 LPS was much stronger than that of complete Freund's adjuvant [13,15,16]. Utilizing the potent KO3 LPS adjuvant, we have established a series of experimental models for various autoimmune diseases, such as ophthalmitis [17,19], thyroiditis [13,16,[20][21][22], pancreatitis [23], hepatitis [24], hemolytic anaemia [25], adrenalitis [26], myocarditis [27], orchitis [28,29], enterocolitis [30] and arthritis [31] in mice. In the present study, we tried to establish experimental murine model for autoimmune sialadenitis by using KO3 LPS adjuvant.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of the adjuvanticity of KO3 LPS was much stronger than that of complete Freund's adjuvant (13-15). Utilizing the potent KO3 LPS adjuvant, we have established a series of experimental models for various autoimmune diseases, such as ophthalmitis (8,27,35), thyroiditis (14,15,30,(33)(34)(35), pancreatitis (26), hepatitis (11), hemolytic anemia (10), adrenalitis (6), myocarditis (9), orchitis (7, 29), and enterocolitis (17) in mice. In the present study, we tried to establish CIA for autoimmune RA by using KO3 LPS adjuvant.…”
mentioning
confidence: 99%
“…The intensity of the adjuvanticity of KO3 LPS was much stronger than that of complete Freund's adjuvant (21)(22)(23)38). Utilizing the potent KO3 LPS adjuvant, we have established a series of experimental models for various autoimmune diseases, such as ophthalmitis (14,32,40), thyroiditis (23,24,35,(38)(39)(40), pancreatitis (31), hepatitis (18), hemolytic anemia (16), adrenalitis (9), myocarditis (15), and orchitis (10,34) in mice. In the present study, we tried to establish a murine experimental model for autoimmune enterocolitis by using KO3 LPS adjuvant.…”
mentioning
confidence: 99%